Evaluating the presence of interspecific hybrids of the sorubims Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum in the middle and inferior Paraná and Uruguay rivers using genetic markers. Issue 6 (22nd November 2018) - Marquez, Alejandro; Tourinho, Julia L.; Errico, Eugenia; Pereira, Alfredo N.
Abstract: The presence of hybrids in the wild represents a threat to the integrity of species. In nature, sympatric species with the capacity to hybridize have mechanisms to prevent introgression, but hybrids originating from aquaculture may pose a threat to natural populations by inevitable escapes from captivity and their interaction with pure individuals in the wild. Given the increased vigour of these hybrids, they may compete better than native individuals. The species of the genus Pseudoplatystoma, commonly named sorubims, are some of the most emblematic species of the La Plata River basin, and are an important part of fisheries and aquaculture in the region. In this work, nuclear and mitochondrial genetic markers were used to evaluate the presence of hybrids in the lower La Plata River basin. Although hybrids of Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum were previously detected in the upper Paraná and Paraguay rivers in Brazil, the presence of hybrids is here extended to the middle section of the Paraná River in Argentina. Hybrids were not found in the lower Paraná River or in the lower and middle sectors of the Uruguay River. This result has implications for conservation, as it shows the impact of the aquaculture of sorubims in the Paraná River, although apparently they have not yet affected the lower and middle Uruguay River.